2001
DOI: 10.3758/bf03200470
|View full text |Cite
|
Sign up to set email alerts
|

Search and selection processes in implicit and explicit word-stem completion performance in young, middle-aged, and older adults

Abstract: In the present investigation, we sought to (1) replicate previous reports of impaired word-stem completion (WSC) priming and cued recall performance in older adults, (2) gain a better understanding of the differential roles of search and selection processes in implicit and explicit WSC, and (3) determine the particular aspects of WSC performance that are influenced by age. Experiment 1 demonstrated that older adults primed and recalled fewer items on a WSC task than middle-aged adults did, who in turn primed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 59 publications
(61 reference statements)
2
42
0
Order By: Relevance
“…With the same cues, explicit retrieval strategies can also be evoked by instructing the participant to retrieve words from the studied list (Word-Stem Cued Recall: WSCR). However, performances in the implicit version of this test are often sensitive to variables that affect explicit memory tests: divided attention (Clarys, Isingrini, & Haerty, 2000) and aging (Chiarello & Hoyer, 1988;Davis et al, 1990;Hultsch, Masson, & Small, 1991;Small, Hultsch, & Masson, 1995;Ryan, Ostergaard, Norton, & Johnson, 2001). Consistent with these results, the WSC test is also affected by depth-of-processing when the shallow study task, in contrast to a deep one, does not engage lexical processing of information (Fay, Isingrini, & Clarys, in press;Richardson-Klavehn & Gardiner, 1998).…”
Section: Introductionmentioning
confidence: 54%
“…With the same cues, explicit retrieval strategies can also be evoked by instructing the participant to retrieve words from the studied list (Word-Stem Cued Recall: WSCR). However, performances in the implicit version of this test are often sensitive to variables that affect explicit memory tests: divided attention (Clarys, Isingrini, & Haerty, 2000) and aging (Chiarello & Hoyer, 1988;Davis et al, 1990;Hultsch, Masson, & Small, 1991;Small, Hultsch, & Masson, 1995;Ryan, Ostergaard, Norton, & Johnson, 2001). Consistent with these results, the WSC test is also affected by depth-of-processing when the shallow study task, in contrast to a deep one, does not engage lexical processing of information (Fay, Isingrini, & Clarys, in press;Richardson-Klavehn & Gardiner, 1998).…”
Section: Introductionmentioning
confidence: 54%
“…We found that, overall, the number of events generated in a script increased with increasing script frequency, suggesting that some aspect of script representations may be subject to frequency effects, like other domains of knowledge (Grafman, 1995 (Spieler & Balota, 2000) or completingword stems (Ryan, Ostergaard, Norton, & Johnson, 2001), our script generation task differs in that it does not rely on external cuing for each event generated. Also, individuals may rely on personal experience when generating scripts.…”
Section: Discussionmentioning
confidence: 94%
“…That is, one and the same grapheme <a> has several phonemic values depending on whether it occurs in open or closed syllables. Experimental evidence from a pronunciation task reported elsewhere (see Schiller, 2000, footnote 8) suggests that native speakers of English have a strong tendency to assign a tense (long) pronunciation to vowels in open syllables (e.g., CV), whereas vowels in closed syllables generally receive lax (short) pronunciations (see also Ryan, Ostergaard, Norton, & Johnson, 2001).…”
Section: Discussionmentioning
confidence: 99%